DO STUDENTS EXPERIENCE “SOCIAL INTELLIGENCE,” LAUGHTER, AND OTHER EMOTIONS ONLINE? - Meyer, Katrina A.; Jones, Stephanie J. (Online Learning, 2012)
Are online activities devoid of emotion and social intelligence? Graduate students in online and blended programs at Texas Tech University and the University of Memphis were surveyed about how often they laughed, felt other emotions, and expressed social intelligence. Laughter, chuckling, and smiling occurred “sometimes,” as did other emotions (e.g., anticipation, interest, surprise). The capacities comprising social intelligence were also experienced “sometimes,” but more frequently in online classes than in non-class-related online activities. The students were mostly likely to present themselves effectively and care about others and least likely to sense others’ emotions. In a comparison of social intelligence capacities in the online course and other non-course-related but online activities (e.g., surfing and gaming), a paired t-test confirmed that the means were different (p < 0.05) and perhaps documented greater occurrence of social intelligence in the online course setting.